Empirical Evaluation of Vocation to Solidarity Economy Using Composite Indicators - Lucia Piani (Sustainability, 2019)
Many scholars today are deepening economic issues by looking at new paradigms based on the relationship between communities and the resources of the territory. The proposals are different, mainly focusing on economic theories such as solidarity economy, a mix of theories and practices based on equity, sustainability, democracy, and reciprocity. The growing legislation on solidarity economy implies to develop tools to support Administrations and Communities throughout the process of effective realization. The aim of this study is to propose a methodology for evaluating the Vocation to Solidarity Economy (VSE) by means of a composite indicator (VSE index) and apply it to the territory of Friuli Venezia Giulia Region in the northeast of Italy. A series of basic factors concerning social, economic, and environmental aspects was defined by multidisciplinary experts and used for VSE index calculations. The spatialization of VSE index allows the assessment of the vocation of territories in supporting the paths to become Communities of Solidarity Economy as defined by a recent regional law. As results of subsequent VSE spatialization we obtain the maps which highlight different characteristics within the Region (i.e. urban/rural relations) helping local administrations to improve current policies towards sustainability.